2011
DOI: 10.1371/journal.pone.0025617
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Pseudomonas aeruginosa from Five Mediterranean Countries: Evidence for Frequent Recombination and Epidemic Occurrence of CC235

Abstract: Several studies in recent years have provided evidence that Pseudomonas aeruginosa has a non-clonal population structure punctuated by highly successful epidemic clones or clonal complexes. The role of recombination in the diversification of P. aeruginosa clones has been suggested, but not yet demonstrated using multi-locus sequence typing (MLST). Isolates of P. aeruginosa from five Mediterranean countries (n = 141) were subjected to pulsed-field gel electrophoresis (PFGE), serotyping and PCR targeting the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
91
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 98 publications
(130 reference statements)
24
91
1
2
Order By: Relevance
“…In addition, previous studies were shown that the presence of the TTSS effector genotypes, especially exoU genotype, correlate with increasing the virulence and resistance to one or more antibiotics. In a study by Agnello et al, they were found that the presence of exoU gene was significantly correlated with flouroquinolones-resistance (4 (23,26). In present study 81.7% and 88.6% of isolates were resistant to ciprofloxacin and levofloxacin; respectively.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In addition, previous studies were shown that the presence of the TTSS effector genotypes, especially exoU genotype, correlate with increasing the virulence and resistance to one or more antibiotics. In a study by Agnello et al, they were found that the presence of exoU gene was significantly correlated with flouroquinolones-resistance (4 (23,26). In present study 81.7% and 88.6% of isolates were resistant to ciprofloxacin and levofloxacin; respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Notably, in our study the percent of exoU + /exoS + isolates were relatively high (20.6%) compared to other studies. Even though exoS and exoU genes are located in different location in P. aeruginosa genome, the simultaneous carriage of both genes less have been reported (23). A possible explanation is that both of the ExoU and ExoS proteins are important for P. aeruginosa survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper surveillance for the emergence of the cytotoxic and MDR P. aeruginosa isolates would be essential for preventing serious P. aeruginosa outbreaks in surgical wards. In fact, further studies are needed to evaluate the clinical outcome of surgical site infections with isolates showing cytotoxic and MDR traits [41].…”
Section: Figmentioning
confidence: 99%
“…MLST analysis showed that PSE305 belonged to the subtype, ST-244. This subtype has been identified in a collection of human wound isolates from the Mediterranean, and in cases of bacteraemia in Asia (Maatallah et al, 2011;Woo et al, 2011). Hence, it is likely that the two isolates compared in this study are derived from the same outbreak.…”
Section: Discussionmentioning
confidence: 90%